EXPERIMENTAL CHARACTERISATION OF 802.11A/G INDOOR PROPAGATION PATTERNS - Hasanain A. H. Al-Behadili (Journal for Technology and Science, 2026)
Objective: The technology of wireless local area network (WLAN) has developed rapidly, and it has become an interesting research topic. The knowledge of the radio propagation characteristics and the environmental information, including the layout of the rooms, the construction materials, and furniture arrangement, is a prerequisite for designing and developing the indoor wireless communication system. So, an exhaustive measurement is essential for studying the radio propagation characteristics. This thesis centres on the path loss for 2.4GHz and 5GHz frequency bands used in wireless Local area network (WLAN), 802.11a and 802.11g standards. Method: Measurements under LOS and OBS environments were conducted, and path loss was calculated. The best fit plots to the measured results are presented. The results from simulations by various models are also examined, and a comparison concerning the accuracy of the models is made. The penetrating loss for some typical partitions is also measured. Results: Some findings are concluded. It is found that the 802.11a 5 GHz frequency band actually suffers more path loss than the 802.11g 2.4 GHz frequency band. In a complex indoor environment, the difference is diminished since various reflections, deflections, and scatter all contribute to signal propagation. Novelty: The results from simulations by various models are also examined, and a comparison concerning the accuracy of the models is made. The penetrating loss for some typical partitions is also measured.